A Note on the Katha Content of Acacia catechu Willd. Growing in Thick and Open forests - Dumbhal, N. P.; Beri, R. M. (Indian Forester, 1981)
Nine samples of the heartwood of Acacia catechu extracted from trees growing in thick forest and in the open, were received from different forest divisions of Gujarat and Maharashtra, and analysed for their contents of katha and cutch. It is observed that there is no definite relation between the katha content of a tree and the density of forest in which it grows. There is, however, no marked variation in the content of cutch present in the trees growing in the thick forest or in the open.